Implantação do serviço de gerenciamento da Terapia Medicamentosa no componente especializado da Assistência Farmacêutica - Kirla Barbosa Detoni (2016)
Medication therapy management (MTM) services have shown clinical, economic and humanistic positive outcomes in several countries; however, implementation remains a challenge. This fact justifies the importance to study in detail the key aspects concerning the stages this process. Implementation research in healthcare represents a critical toolfor the provision of scientific evidence to expand programs in healthcare. Despite that, this type of research is often neglected. Thus, this study aimed to understand the MTM implementation process in a Specialty Pharmacy unit, in the state of Minas Gerais. The construction of the service began from a partnership between the Pharmaceutical CareStudy Centre of the Federal University of Minas Gerais and the manager of the pharmacy in September 2014. Ethnography was used as the methodology, conducted from the beginning of the implementation until February 2016. Multiple data collection methods were used. Semi-structured interviews were conducted with twelve members ofthe scenario: two managers; three pharmacists; the clinical pharmacist partner; two service leaders and four patients followed up in MTM. Notes from field diaries were also used, as a result of participant observation, from the two pharmacists responsible for the implementation. Two central themes emerged from the analysis and interpretation ofresults: "Optimizing the implementation of MTM services: criteria to improve the success of the process" and "Specialty Pharmacy Peculiarities. The first includes eleven categories, which can be translated into conditions to enhance the success of the MTMimplementation in this pharmacy. The results showed that for the service to become a reality in the unit, the presence of a professional with a profile for patient care of people, properly trained for the MTM, is of paramount necessity. Different professionals should administer the management of the dispensing and the clinical service separately. Devotion to care requires a metamorphosis in professional practice and the development of other skills different from those developed by the traditional pharmacists, focused on drug dispensary. Despite the challenges experienced, the MTM implementation in the Specialty Pharmacy proved to be feasible. The lack of other health professionals on the site and the fact of it being a dispensing unit have not presented as barriers to offering a direct care service. Although the study was conducted in a specific scenario, it is believed that the results can assist the implementation of MTM services in other healthcare environments. It is noted to pharmacists and managers the importance of considering these aspects before and during deployment, maximizing the success of the process.